A two-tier strategy for priority based critical event surveillance with wireless multimedia sensors - Bhatt, Ravindara; Datta, Raja (Wireless networks, 2016)
Surveillance plays a vital role in protecting infrastructure facilities of a country and improving detection of cross-border activities. Compared to traditional surveillance systems, wireless multimedia sensor networks (WMSN) provide distinct advantages. In this paper we consider the problem of critical event surveillance in a region of interest with the help of WMSN. The challenge here is deployment cost, energy-efficient routing and preservation of coverage and connectivity of the network. To keep the deployment cost minimum, we propose a two-tier strategy consisting of (a) densely deployed low cost audio tier nodes and (b) sparsely placed high cost video tier nodes to monitor critical events occurring in a given area. The audio nodes perform the preliminary event detection task, whereas, the base station activates the rotatable-video nodes on a demand basis. Depending upon the cost of potential damage, an event is assigned a priority, and based upon that priority an event is assigned either energy efficient or a delay tolerant path along the audio and video tiers. We also propose two integer linear programming formulations MEAT and MEVT for minimization of energy consumption in audio and video tiers separately. We then present two approaches, namely Greedy and DCSEG, and compare them with a popular existing approach under various scenarios. Simulation results show considerable reduction in the number of active audio and video sensor nodes per event which leads to low deployment cost and reduction of average energy consumption in the network.